Marathon and Thermopylae in the mémoire collective - Kulesza, Ryszard (Anabasis. Studia Classica et Orientalia, 2011)
The majority of Greeks remembered the battles of Marathon, Thermopylae, Salamis and Plataeae; but the future was to belong not to the pan-Hellenic Salamis or Plataeae, but to the Marathon, appropriated by the Athenians, and Thermopylae, which the Spartans made their own. The battles of Marathon and Thermopylae are viewed by us only from the perspective of the Greek sources, and some lacunas are obvious even in those. In both cases the events were quickly mythologized. In Athens Marathon almost immediately grew into a symbol of the Greeks’ struggle with the barbarians (as seen from The Persians by Aeschylus,). The first epitomised love of freedom, the latter – enslavement. Marathon became the object of pride for the Athenians, who were the first among the Greeks to oppose the invasion of the eastern barbarians. In Thermopylae, a stone lion and the famous epitaph by Simonides commemorated the death of the Spartans. Perhaps it is only there that lies the source of the general, and not entirely correct, conviction that a Spartiate could only be victorious or die, tertium don datur. With the passage of time, both battles gained in importance with respect to politics. Marathon has long been an element of the European mémoire collective. Yet the star of Marathon rose fully in the 19 th century, when it became an inspiration for poets (e.g. Elizabeth Barrett Browning and George Byron) and the symbol of the Greek war of independence. It was, of course, present also in the history of Poland. Throughout the 19 th , 20 th and early 21 st century, “Thermopylae” seem to have replaced “Marathon” as the symbol of a heroic fight for freedom. To an increasing number of people – not only in Europe, but throughout the world – “Marathon” and “Thermopylae” are lieux de mémoire, a confirmation of belonging to a system of values for which the Greeks fought (consciously or not, but that is another story) in the early fifth century B.C.